Opportunities for optimizing fungal biological control agents for long-term and effective management of insect pests of orchards and vineyards: a review - Wallis, Christopher M.; Sisterson, Mark S. (Frontiers in Fungal Biology, 2024)
Novel tactics for controlling insect pests in perennial fruit and nut crops are needed because target pests often display decreased susceptibility to chemical controls due to overreliance on a handful of active ingredients and regulatory issues. As an alternative to chemical controls, entomopathogenic fungi could be utilized as biological control agents to manage insect pest populations. However, development of field ready products is hampered by a lack of basic knowledge. Development of field ready products requires collecting, screening, and characterizing a greater variety of potential entomopathogenic fungal species and strains. Creation of a standardized research framework to study entomopathogenic fungi will aid in identifying the potential mechanisms of biological control activity that fungi could possess, including antibiotic metabolite production; strains and species best suited to survive in different climates and agroecosystems; and optimized combinations of entomopathogenic fungi and novel formulations. This mini review therefore discusses strategies to collect and characterize new entomopathogenic strains, test different potential mechanisms of biocontrol activity, examine ability of different species and strains to tolerate different climates, and lastly how to utilize this information to develop strains into products for growers.